Forest restoration treatments increase native plant diversity but open the door to invasion in the Colorado Front Range - Mahood, Adam L.; Stevens-Rumann, Camille S.; Rhea, Allison E.; Ritter, Scott M.; Barrett, Kevin; Fornwalt, Paula J.; Barnard, David M. (Forest ecology and management, 2025)
Forest restoration treatments in dry conifer forests of the western United States are often done with objectives to move current forest structure toward historical conditions and, in turn, increase the system’s resilience to future wildfires. But little is known about their effects on understory plant composition, particularly over the long-term. This is especially true in the Colorado Front Range (CFR). We used a before/after control/impact study design to assess the effects of mechanical forest restoration treatments on forest structure, surface fuels and understory plant composition 1, 5, and 10 years after treatment. Five and 10 years after treatment, treated areas had lower basal area and tree density, and higher quadratic mean diameter, consistent with treatment objectives. Treated areas also had higher native understory plant cover and richness, and higher graminoid cover. Species accumulation curves showed treatment-wide increases in native richness at 5 years post-treatment, and further increases at 10 years, with a net increase of 47 native species in treated areas compared to 11 in untreated controls. However, treatments also had higher relative numbers of non-native plant species, and increased probability of non-native plant invasion, though the overall level of invasion was low. Native richness, native cover and graminoid cover were more strongly associated with stand structure and topography, while non-native invasions were more strongly associated with moisture deficit. This suggests that climate played a greater role in enabling the introduction of species than changes in stand structure affected by treatment. In the CFR, forest restoration treatments can benefit the native understory, but also provide an opening for invasion in relatively uninvaded sites. ●Forest restoration treatments to restore historical forest structure are being conducted at a broad scale.●Little is known about their long-term effects on understory plants in the Colorado Front Range.●Treatments increased native plant species richness and cover ten years after treatment.●But they also increased invasions and the percent of non-native species.●Relative cover of non-native was very low, so management interventions may be effective.